Does board gender diversity play an important role in environmental and corporate performance? - Agus Dwianto; Annisa Qurrota A'yun; Mey Ayu Lestari; Daniel Kassim Sesay; Ibrahim Rahman Turay (Akuntansi dan Teknologi Informasi, 2024)
This research investigates the impact of Return on Assets (ROA), Debt to Equity Ratio (DER), Sales Growth, and Gender Diversity on Environmental Performance (EP) among 75 companies listed on the Indonesia Stock Exchange participating in the PROPER program from 2019 to 2022. The study employs a random effects model. The findings indicate that ROA, DER, Sales Growth, and Gender Diversity significantly influence EP. Specifically, Firm Size (FZ) moderates the impact of DER on EP. However, Firm Size does not significantly moderate the effects of ROA, Sales Growth, and Gender Diversity on EP. The research provides insights into factors contributing to the financial performance of companies and the moderating role of firm size. The novelty of the study lies in the moderating role of firm size in the relationship between ROA, DER, Sales Growth, and Gender Diversity with environmental performance. The research contributes to legitimacy, stakeholder, and agency theories. Policymakers can leverage these insights to formulate strategies that encourage corporate sustainability. This study offers valuable information for companies aiming to enhance both environmental and financial performance, ultimately contributing to broader societal well-being.